IMC growth mechanism of Sn58Bi/Cu solder joints and its effect on the coarsening of the Bi phase - Min Shang; Chenyu Li; Yanchen Wang; Xiangxu Chen; Yuanbang Zhao; Jingli Ke; Yunpeng Wang; Haitao Ma; Jun Chen (Journal of Materials Research and Technology)
In the use of Sn58Bi solder alloy, the abnormal enrichment and coarsening of Bi phase in solder joints and the excessive growth of IMC seriously affect its service reliability, among which, the IMC's reaction mechanism and evolution, the influence on the coarsening of the Bi phase within the solder and the coarsening process are not yet clear. The study found that the initial type and morphology evolution of IMC of Sn58Bi/Cu solder joint are influenced by soldering temperature and cooling rate, attributed to the differences in dissolution and diffusion of Cu in Sn58Bi, resulting in different initial appearances of Cu6Sn5 and Cu3Sn; The temperature and cooling rate affect whether Cu6Sn5 and Cu3Sn are directly generated by the reaction of Cu atoms in the substrate or appear through the consumption of Cu3Sn or Cu6Sn5; The cooling rate affects the IMC morphology evolution of top-view; Based on this, it was cleared that Sn58Bi/Cu solder joints follow four interfacial reaction mechanisms. Meanwhile, the evolution of Bi phase in the solder is affected by the growth of IMC in Sn58Bi/Cu, resulting in varying degrees of coarsening. Analysis suggests that the entire coarsening process involves the aggregation, dissolution, and separation of Bi phase. This article elucidates the reaction mechanism of IMC growth at the Sn58Bi/Cu solder joint interface and its influence on the coarsening of Bi phase inside the solder, providing theoretical support for improving the reliability of Sn58Bi solder in the future.